For a different pedagogy. Three voices and three hearts - Hernández Méndez, Griselda; Hernández Méndez, Edith; Malpica Ichante, Susano (IE Revista de Investigación Educativa de la REDIECH, 2021)
The purpose of this paper is re-signifying the experiences of the members of a research group of the Universidad Veracruzana about the use of different pedagogical approaches and strategies that they were not accustomed to use, but, once trained within the framework of two projects, they managed to put it into practice in their classrooms. For experiences interpretation, the narrative biographical research and the in-depth interview as ideal techniques were taken up as inquiry approach. The questions guide revolved around two moments: before being trained in the theoretical and methodological principles underlying these projects, and after having been trained and having implemented all this in the classrooms. The stories intersected with some elements of the revolving projects around the complex approach and critical theory. The teachers identified disappointment, confusion and even mistakes made, but also possibilities of training students from a different pedagogy focused on the local perspective under the principles of complex and critical thinking. The results demonstrate the urgency of a new pedagogy that responds to local, social-human needs and, above all, to those of the contemporary student body, more often than not alienated and unconscious by the effects of colonization, globalization and modernization.